REMODELLING AND REPOSITIONING OF COURT’S MEDIATION IN INDONESIA - R. Benny Riyanto (Fakultas Hukum, Universitas Diponegoro, 2016)
This article is intended to explain the failure of the use of mediation in Indonesia, particularly mediation which is integrated with the court (court connected mediation). The focus of the problem in this study is about the ideal model of court connected mediation as a strategy to achieve the hope of strengthening and to maximize the function of judiciary institutions in resolving dispute in Indonesia. A method of socio-legal research is used to reveal things that make mediation has not worked effectively in resolving civil case in court. This study resulted that the practice of mediation in civil court is very limited, especially dealing with a model applied by mediators, so it is not always appropriate to the situation faced by the parties in disputes. Moreover, although the Supreme Court Regulation allows co-mediation, in practice, it is never implemented. Even court connected mediation has become part of the dispute because it has been registered and published to public. So that it becomes a non-legal factor that influence the parties to reach agreement. Keywords : mediation, mediator, civil case, model, court.